Job stress, work attitude and job satisfaction affecting absenteeism among employees in Pejabat Pendidikan Daerah Pasir Mas / Abdul Latif Omar - Omar, Abdul Latif (2015)
A study was conducted to determine the predictors that affecting to employee absenteeism at the workplace. The study analyzed whether or not there is a significant relationship between job stress, work attitude, and job satisfaction among employees in the workplace. Data were collected by using questionnaires from 100 employees from PPD Pasir Mas and any other organization that located nearer Pasir Mas's area. The unit of analysis was individual employees with the instrument of questionnaire and using five-point likert scale to measure the variables. The questionnaire was used to collect and use SPSS version 16.0 sofware to measure frequency analysis, reliability for each items, multiple regression analysis, descriptive analysis and t-test analysis. The results have been accomplished in this study in the attempt to explain which factors that contributes to absenteeism. However, only job stress and job satisfaction are significantly influencing the absenteeism in the organizations, which means absenteeism problem in PPD Pasir Mas cause by job stress and job satisfaction. Meanwhile, work attitude has no influence to the absenteeism in the organization.